Local economic development: new generations of actors, policies and instruments for Africa - Helmsing, A.H.J. (Bert) (2003)
As decentralisation advances, the question of local economic development acquires more significance. How can local governments and other local actors such as local producers and their associations, community based organisations, as well as NGOs and donors contribute to local economic development and poverty reduction? This article begins by examining how the context for local economic development has drastically changed. It stresses lack of demand and the absence of meso-level institutions, i.e., institutions at the level of sector and area. Their absence deters investment responses by enterprise or business development. The first seeks to facilitate household economic diversification as an essential stra tegy of rural and urban livelihood; the second, enterprise development, seeks specialisation of the local economic base. These two lines are complemented by a third category, namely locality development, designed to create local public goods and positive externalities. The final section elaborates on the principal actors and their roles, stressing the importance of joint action and collective learning. Local governments have an important facilitating role, creating a favourable business environment and infrastructure conditions, and to contribute to convergence in decision-making. - Reproduced.
Keywords: Local government - Africa; Economic and social development - Africa; Economic and social development